The Tomato Spotted Wilt Virus Genome Is Processed Differentially in its Plant Host Arachis hypogaea and its Thrips Vector Frankliniella fusca - Fletcher, Stephen J.; Shrestha, Anita; Peters, Jonathan R.; Carroll, Bernard J.; Srinivasan, Rajagopalbabu; Pappu, Hanu R.; Mitter, Neena (Frontiers in Plant Science, 2016)
Thrips-transmitted tospoviruses are economically important viruses affecting a wide range of field and horticultural crops worldwide. Tomato spotted wilt virus is the type member of the Tospovirus genus with a broad host range of more than 900 plant species. Interactions between these viruses and their plant hosts and insect vectors via RNA interference pathways are likely a key determinant of pathogenicity. The current investigation, for the first time, compares biogenesis of small RNAs between the plant host and insect vector in the presence or absence of TSWV. Unique viral small interfering RNA (vsiRNA) profiles are evident for Arachis hypogaea (peanut) and Frankliniella fusca (thrips vector) following infection with TSWV. Differences between vsiRNA profiles for these plant and insect species, such as the relative abundance of 21 nt and 22 nt vsiRNAs and locations of alignment hotspots, reflect the diverse siRNA biosynthesis pathways of their respective kingdoms. The presence of unique vsiRNAs in F. fusca samples indicates that vsiRNA generation takes place within the thrips, and not solely through uptake via feeding on vsiRNAs produced in infected A. hypogaea. The study also shows key vsiRNA profile differences for TSWV among plant families, which are evident in the case of A. hypogaea, a legume, and members of Solanaceae (S. lycopersicum and N. benthamiana). Distinctively, overall small RNA biogenesis in A. hypogaea is markedly affected with an absence of the 24 nt small RNAs in TSWV-infected plants, possibly leading to wide-spread molecular and phenotypic perturbations specific to this species. These findings add significant information on the host-virus-vector interaction in terms of RNAi pathways and may lead to better crop and vector specific control strategies.